UFS Intradigital: análise da governança eletrônica para concepção de um protocolo para integração da transformação digital - Daier, Gustavo Torres de Brito (2023)
The Federal Public Administration (FPA) has been implementing and enhancing Electronic Governance processes, utilizing tools such as the Information Technology Resources Management System – in pursuit of realizing the Federal Digital Government Strategy (FDGS) 2020-2023 – and the National System for Digital Transformation – which oversees the Brazilian Digital Transformation Strategy (E-Digital) 2022-2026. Additionally, the Digital Government Law (DGL) also arrives with extensive principles and guidelines for compliance by federal, state, municipal, and District Federal entities. At the Federal University of Sergipe (UFS), a structuring of its governance policy is already in development, enabling the continuous development of best practices in Electronic Governance within the institution. However, it does not yet demonstrate the necessary strategic pursuit of Digital Transformation (DT) in its processes. Considering the outlined scenario, the present study aimed to analyze the structure of Electronic Governance and the integration of UFS's Digital Transformation processes, in relation to federal norms and regulations. Through a basic qualitative research approach, utilizing secondary data (documentary research) and primary data (interviews with members of the UFS Institutional Governance Committee), description, triangulation, and categorization were conducted using Bardin's content analysis technique, incorporating elements of analysis from the 5 dimensions derived from the study's specific objectives. This allowed for the identification of advanced alignment between UFS's Electronic Governance instruments and federal norms, regulations, and guidelines, with electronic governance and digital transformation actions that enabled their inclusion in a four-stage integrated Digital Transformation model, classifying UFS's work processes at the third stage – Digital Transformation. Moreover, the study presented results with sufficient insights to construct a technical report with seven suggestions and a diagram of integrated actions aimed at the Digital Transformation of its work processes: the UFS Intradigital Protocol.